Free Vascularized Dermofat Flap For Contouring Maxilla In Fibrous Dysplasia Patients - Atmodiwirjo, Parintosa; Martina, Nungki Ratna (Jurnal Plastik Rekonstruksi, 2012)
Fibrous dysplasia is a disease that causes bone thinning and growth of lesions in one or more bones and leads to bone weakness and scar formation within the bones. Especially when involving the skull or facial bones, the lesions can cause externally visible deformities. We reported one case of fibrous dysplasia of the maxilla reconstructed in our Plastic Surgery Division of Cipto Mangunkusumo Hospital. Data was taken from the medical and surgery records. In this case, we used the Antero Lateral Thigh (ALT) flap to reconstruct the maxilla and facial contour in 26 years old girl with fibrous dysplasia. After the operation we had daily observation to evaluate the blood flow to the flap and it had satisfactory result without any complication. Ultimately, free vascularized dermofat flap with ALT seems to be suitable for craniofacial contouring surgery, in this case for contouring maxilla. Facial contour could further be improved after secondary reshaping of the healed flaps. This led to nearly perfect long-term facial symmetry in all cases. The ALT proved to be a reliable donor site, providing enough well-vascularized fatty tissue for facial contour augmentation.